Pemanfaatan Cuka Aren Sebagai Herbisida Alami Untuk Membasmi Gulma - Topanus Tulak*; Roberto Salu Situru; Zainal Batatta (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Weeds are plants that disturb or harm human interests, especially in the process of plant growth. Weeds are one of the main factors that can cause a decrease in agricultural yields. Weeds can also harm farmers or agricultural businesses by reducing the quality of agricultural production. Weed control or weeding can be done by means of preventive, mechanical, biological, technical culture, chemical and synthetic. Weed control with herbicides is the main choice compared to other methods because they are considered more effective in controlling weeds, besides being more cost-effective and time-effective. Weeding is an effort that must be done against it so as not to inhibit plant growth. With this activity, it can increase the community's ability to use palm vinegar as a natural herbicide to help farmers increase their crop yields, reduce the use of incendiary herbicides in weed control so as to increase the community's ability in organic farming.